Struktur Komunitas Fitoplanton di Waduk Cacaban Kabupaten Tegal - Dian Setyowati; Diana Retna Utarini Suci Rahayu; Agatha Sih Piranti (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2022)
Phytoplankton has an important role in an aquatic ecosystem because it is autotrophic and also a source of natural food for fish. Phytoplankton will interact with other biotic factors to form a community structure that is useful for the sustainability of the ecosystem Therefore, this research is needed to determine the phytoplankton community structure in Cacaban Reservoir because the community structure can shows the water conditions. The purpose of this reserch was to determine the composition, abundance, and diversity of phytoplankton at each station and the most dominant type of phytoplankton in Cacaban Reservoir. The result showed that there are 18 species of phytoplankton in Cacaban Reservoir. The four phytoplankton divisions found were Chlorophyta with 8 species, Bacillariophyta with 5 species, Cyanophyta with 3 species, and Charophyta with 2 species. The abundance is in the medium category, with the abundance of Chlorella sp. the highest at stations I, III and IV; and Microcystis sp. at stations II and V. The diversity index ranges between 1,227-1,766 and was in the low category which indicates low community stability. The dominance index range between 0,648-0,791 and was in the high category. The dominant phytoplankton in the Cacaban Reservoir is from the Chlorophyta division, which is also a type favored by fish.